1990
DOI: 10.1161/01.res.66.2.511
|View full text |Cite
|
Sign up to set email alerts
|

Mast cells in the rat heart during normal growth and in cardiac hypertrophy.

Abstract: Mast cells in rat hearts were studied quantitatively during normal postnatal growth and in two types of cardiac hypertrophy. Normally, cardiac mast cell density in 11-12-day-old animals is very low, but increases markedly in the following 2-3 weeks to its highest values, with a subsequent decline toward adult values. At the peak of mast cell density, the percentage of mast cells in close proximity to capillaries is also highest. In adult animals, mast cell counts are significantly higher in the right ventricle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
38
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…This explains why DSCG applied at the end of hypoxic exposure has no effect on pulmonary vascular resistance and vascular remodeling. In contrast, Rakusan et al [26] reported a persistent increase in the number of mast cells in hearts of rats acclimatized to high altitude for 4 weeks. The interesting finding of their study is that a similar increase in the heart mast cell density was not found in rats with renal hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…This explains why DSCG applied at the end of hypoxic exposure has no effect on pulmonary vascular resistance and vascular remodeling. In contrast, Rakusan et al [26] reported a persistent increase in the number of mast cells in hearts of rats acclimatized to high altitude for 4 weeks. The interesting finding of their study is that a similar increase in the heart mast cell density was not found in rats with renal hypertension.…”
Section: Discussionmentioning
confidence: 93%
“…Mast cells may also play a role in hypertensive heart disease. Although changes in mast cell number were not observed in hearts from a Goldblatt model of hypertension in rats (30), studies in spontaneously hypertensive rats led investigators to suggest that mast cells play a role in the cardiac fibrosis and hypertrophy that occur in hypertension, possibly due to the secretion of cytokines and growth factors (26,32). Experiments also showed that the progression from compensated hypertrophy to decompensated failure in a pressure overload model is largely prevented in mast celldeficient mice or in wild-type mice treated with tranilast, a mast cell stabilizer (15).…”
mentioning
confidence: 78%
“…It has been reported that cardiac mast cell density increases during the first month of life in rats and then declines to a lower adult level (30); however, the role of mast cells in normal cardiac development and function is unknown. The present experiments using a mast cell-deficient rat model were designed to determine whether mast cells affect cardiac function in adults in the absence of insult.…”
mentioning
confidence: 99%
“…Mast cells are present in most tissues and are often found in close proximity to blood vessels, including capillaries and postcapillary venules (18)(19)(20). Upon Adenosine has potent effects on both the cardiovascular and immune systems.…”
Section: Introductionmentioning
confidence: 99%